Drought and Competition With Ivyleaf Morningglory (Ipomoea hederacea) Inhibit Corn and Soybean Growth - Westbrook, Anna S.; Han, Rongkui; Zhu, Jinwen; Cordeau, Stéphane; DiTommaso, Antonio (Frontiers in Agronomy, 2021)
Agricultural impacts of climate change include direct effects on crop plants and indirect effects, such as changes to the distributions and competitiveness of weed species. In the northeastern United States, warming temperatures are likely to result in periods of soil moisture deficit and changes to weed communities. Ivyleaf morningglory (IMG, Ipomoea hederacea Jacq.) is a summer annual vine that competes with field crops and interferes with harvesting. Climate change may increase the competitive effects of IMG on northeastern U.S. field crops. We conducted a greenhouse study to evaluate the effects of IMG on corn (Zea mays L.) and soybean [Glycine max (L.) Merr.] under drought and non-drought conditions. The drought treatment was crossed against an IMG competition treatment with five levels: one crop plant without IMG plants, one crop plant with one, two, or three IMG plants, and one IMG plant without crop plants. Both drought and IMG (presence or biomass) reduced the biomass of corn and soybean (P < 0.05). Drought and IMG (presence) reduced soybean pod production (P < 0.001). IMG biomass was reduced by drought and the presence of corn (P < 0.001). Across all competition treatments, drought reduced IMG biomass by 71% in the corn experiment and 79% in the soybean experiment, compared with a corn biomass reduction of 50% and a soybean biomass reduction of 58%. Well-designed management programs should mitigate the risks associated with stressors such as IMG and drought, which may threaten northeastern U.S. field crop production under climate change.